KULINER JADUL EMPAT NEGERI: THE MANIFESTATION OF GUSJIGANG PHILOSOPHY IN BUKA LUWUR SUNAN KUDUS 1444 H - Munachifdlil Ula, Ahmad Nilnal; Mu’ayyadah, Mu’ayyadah; Mulyani, Ulva Rizky (Analisa: Journal of Social Science and Religion, 2022)
The background of this article is the preservation of the local tradition of Kudus which is the focus of attention. Buka Luwur is the tradition of uncovering the white robe of Sunan Kudus’s Tomb. Gusjigang that stands for ngaji (studying-learning), bagus (kind-good) pinter dagang (smart in business-trading) means good in reciting Quran and clever in trading. The culinary of Jadul Empat Negeri symbolizes myriad of values. This study aims to define the meaning of Gusjigang, and, to describe the relevance of “Kuliner Jadul Empat Negeri” in Buka Luwur Sunan Kudus ceremony to the Gusjigang philosophy.” The descriptive qualitative research method was applied in this article with the type of literature. Researcher answered the question formulation with data and content analysis obtained from library sources, including scientific and non-scientific journals. However, the researcher also conducted direct observations during the “Kuliner Jadul Empat Negeri” event. The results of the study indicate the meaning of Gusjigang serves as guidance for Kudus citizens in trading and studying learning on religious and secular matters. Furthermore, the meaning of “Kuliner Jadul Empat Negeri” is a manifestation of Sunan Kudus’ Gusjigang teachings. The relevance of the three is to interrelate the values contained in each focus. Work ethic, togetherness, brotherhood, and Islamic education are among these values. In conclusion, the event of culinary of Jadul Empat Negeri” symbolizes Gusjigang philosophical points in the Buka Luwur Sunan Kudus ceremony 1444 H.